Enteral nutrient supply for preterm infants: commentary from the European Society of Paediatric Gastroenterology, Hepatology and Nutrition Committee on Nutrition - Agostoni, C; Buonocore, G; Carnielli, V P; De Curtis, M; Darmaun, D; Decsi, T; Domellöf, M; Embleton, N D; Fusch, C; Genzel-Boroviczeny, O; Goulet, O; Kalhan, S C; et al. (Journal of pediatric gastroenterology and nutrition, 2010)
The number of surviving children born prematurely has increased substantially during the last 2 decades. The major goal of enteral nutrient supply to these infants is to achieve growth similar to foetal growth coupled with satisfactory functional development. The accumulation of knowledge since the previous guideline on nutrition of preterm infants from the Committee on Nutrition of the European Society of Paediatric Gastroenterology and Nutrition in 1987 has made a new guideline necessary. Thus, an ad hoc expert panel was convened by the Committee on Nutrition of the European Society of Paediatric Gastroenterology, Hepatology, and Nutrition in 2007 to make appropriate recommendations. The present guideline, of which the major recommendations are summarised here (for the full report, see http://links.lww.com/A1480), is consistent with, but not identical to, recent guidelines from the Life Sciences Research Office of the American Society for Nutritional Sciences published in 2002 and recommendations from the handbook Nutrition of the Preterm Infant. Scientific Basis and Practical Guidelines, 2nd ed, edited by Tsang et al, and published in 2005. The preferred food for premature infants is fortified human milk from the infant's own mother, or, alternatively, formula designed for premature infants. This guideline aims to provide proposed advisable ranges for nutrient intakes for stable-growing preterm infants up to a weight of approximately 1800 g, because most data are available for these infants. These recommendations are based on a considered review of available scientific reports on the subject, and on expert consensus for which the available scientific data are considered inadequate.